A corpus-based analysis of critical thinking through interactional metadiscourse in pre-service EFL teachers' writing - Yilmaz, Selahattin; Ilerten, Ferda (MEHMET TEKEREK, 2024)
Critical writing seeks to enhance university students' ability to think causally and reason effectively, and this improvement should be evident in their language use in the assignments. An example of such language is interactional metadiscourse, the expression of attitudes and opinions in line with the intended audience. In pursuit of these objectives, this study investigated the textual characteristics of critical thinking by examining interactional metadiscourse markers (MDMs) in the critical response papers authored by English Language Teaching (ELT) undergraduate students throughout a semester at a Turkish state university. The findings revealed shifts in the use of interactional MDMs by the end of the semester. While markers for engagement, hedging, and boosting remained prevalent across various tasks, the utilization of self-mentions an d attitude markers declined, indicating a transition from the students' sharing personal opinions and experiences to relying on evidence from research in academic texts to support their arguments. Additionally, the study highlighted the impact of topic selection on how students incorporated metadiscourse markers into their response papers.
Keywords: Critical thinking; English for academic purposes; Metadiscourse; Pre-service teacher education; Second language writing; STANCE; L1; Education & Educational Research